Effect of Project-Based Learning (PjBL) Model Assisted by Geospatial Technology on Students' Creative Thinking Skills - Palupi, Egidhea Disnaya; Wirahayu, Yuswanti Ariani (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
In the era of globalization and technological developments, education plays an important role in preparing students' future. One of the geospatial technologies that can be utilized is Google Earth, which allows students to access spatial information visually and interactively. Teachers need to use the Project Based Learning (PjBL) learning model to determine the effect of students' creative thinking skills. This study examines the effect of a project-based learning model supported by geospatial technology on the creative thinking skills of grade X students at SMAN 2 Batu. The method used was a quasi-experiment with a post-test-only control group design. Students of class X5 became the experimental class that applied the PjBL model, while class X6 was a control with conventional learning. The results showed that the mean value of the creative thinking skills post-test was higher (84.84) compared to the control class (74.00). The results of hypothesis testing using the Mann-Whitney U-Test non-parametric test showed Sig. (2-tailed) 0.000<0.05, which indicates a significant difference in the post-test scores of the two classes, which means that the hypothesis (H0) is rejected and the hypothesis (Ha) is accepted, so it can be concluded that the application of the Project Based Learning (PjBL) model assisted by geospatial technology has a significant effect on students' creative thinking skills.